(untitled) (UCC Law Journal, 2024)
The ECOWAS integration schemes envisaged that the place of individuals will require an in-depth consideration of the role individuals play, both as beneficiaries of integration (particularly as it relates to trade liberalisation, free movement, residence and establishment) and also, as potential victims of the rough side of integration, which will necessarily require the examination of how individuals may enforce their rights under the integrative instruments. Although several attempts at creating effective regional integrative arrangements in ECOWAS have been made, it is disheartening to state that economic activities involving individuals within the ECOWAS sub-region remain at its lowest ebb. This study reiterates that despite the efforts made to ensure that the ECOWAS integration agenda is realisable, it is in doubt whether citizens of the Community have actually felt free to move in, live and establish in any part of the sub-region of their choice without any attack either on their persons or their investments. This study reveals that attacks on foreigners and their businesses in the ECOWAS region have become legendary and remain a hindrance to the realisation of the ECOWAS objectives envisaged in its legal instruments. In view of the above, this study therefore, recommends that until these identifiable challenges are curtailed, member States may lean towards adopting a protectionist approach to its economic and citizenry affairs and thus, may not be favourably disposed to ensuring full implementation of the ECOWAS Protocols on the right of movement, residence and establishment.